2012
DOI: 10.1016/j.jneuroim.2012.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and magnetic resonance imaging features of multiple sclerosis with autoreactive antibodies in Ishikawa Prefecture, Japan

Abstract: Previous reports of multiple sclerosis (MS) with autoantibodies might include neuromyelitis optica (NMO). We investigated the frequency of autoreactive antibodies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…One study investigated the spinal cord of patients with NMO using axial magnetic resonance imaging (MRI) and found that over 60% of lesions exhibited T2-hyperintense regions that comprised of more than 50% of the cord area, and that these regions were mainly located in the central grey matter [20]. In relation to other autoimmune diseases and auto-reactive antibodies, 70% of patients with NMO have at least one auto-reactive antibody (except for NMO-IgG), and thus it seems that systemic autoimmune diseases including SLE are fairly similar to NMO [25].…”
Section: Neuromyelitis Opticamentioning
confidence: 99%
“…One study investigated the spinal cord of patients with NMO using axial magnetic resonance imaging (MRI) and found that over 60% of lesions exhibited T2-hyperintense regions that comprised of more than 50% of the cord area, and that these regions were mainly located in the central grey matter [20]. In relation to other autoimmune diseases and auto-reactive antibodies, 70% of patients with NMO have at least one auto-reactive antibody (except for NMO-IgG), and thus it seems that systemic autoimmune diseases including SLE are fairly similar to NMO [25].…”
Section: Neuromyelitis Opticamentioning
confidence: 99%